Strategies for research in constructivist international relations - Klotz, Audie, 1962- (International relations in a constructed world., 2007)
Constructivism's basic premise - that individuals and groups are shaped by their world but can also change it - may seem intuitively true. This book lays out concepts and tools for those seeking to apply the constructivist approach in research. It is intended for those trying to sort out appropriate methods for empirical research.